2020
DOI: 10.7717/peerj.8254
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on searching for peri-nuclear NeuN-positive cells

Abstract: The aim of this study was to find out neuron (-like) cells in peripheral organs by cell markers in rats. Adult male Sprague-Dawley rats were anaesthetized. Their organs including brain, heart, lung, liver, kidney, stomach, duodenum, and ileum were harvested. The mRNA and protein in these organs were extracted. RNA sequencing (RNA-Seq) was carried out, and NeuN, a ''specific'' marker for neuronal soma, was assayed with Western blotting. The sections of the aforementioned organs were obtained after a routine fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…We observed NeuN expression in both cell lines, but in traditional PC12 cells, expression was localised to cell nuclei, and in adherent cells, it occurred for the whole cell, both in the nucleus and the cytoplasm. For many years, NeuN was considered a specific marker that allows the recognition of adult neurons [38]. Recent studies, however, have shown that quantitative assessment of this protein does not give reliable information, because its expression occurs in many tissues as well as many cell lines that are not-neuronal cells [38,53,54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed NeuN expression in both cell lines, but in traditional PC12 cells, expression was localised to cell nuclei, and in adherent cells, it occurred for the whole cell, both in the nucleus and the cytoplasm. For many years, NeuN was considered a specific marker that allows the recognition of adult neurons [38]. Recent studies, however, have shown that quantitative assessment of this protein does not give reliable information, because its expression occurs in many tissues as well as many cell lines that are not-neuronal cells [38,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, NeuN was considered a specific marker that allows the recognition of adult neurons [38]. Recent studies, however, have shown that quantitative assessment of this protein does not give reliable information, because its expression occurs in many tissues as well as many cell lines that are not-neuronal cells [38,53,54]. Additional assessment is necessary, whether NeuN is expressed in or around the nucleus or in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubb3 is a neuron-specific class III β-tubulin that mainly localizes in neural axons [38], thus revealing important processes of neurite development in PK 11195-treated cells, as were observed microscopically. Although NeuN is commonly localized in neuronal soma, recent studies have reported its cytoplasmic localization in several peripheral tissues-such as heart, liver, lung, and kidneys-where NeuN has functions other than neuronal differentiation, specifically those related to RNA splicing [39]. Expression of NeuN in undifferentiated P19 stem cells supports these non-neural functions of NeuN.…”
Section: Discussionmentioning
confidence: 90%
“…Some of the speci c proteins expressed by neural cells can be used as their markers. In particular, NeuN was widely accepted as the "speci c" cell marker for neurons [37].In the rats after MCAO/R surgery, the number of neurons decreased, treatment with DHA increased the number of NeuN + cells in the cerebral ischemia penumbra, GSK0660 redud the protective effect of DHA on NeuN + cells. In combination with Hematoxylin-Eosin Staining, the ischemic cortical neurons showed atrophic morphologcey, accompanied by nuclear pyknosis, fragmentation and dissolution.…”
Section: Discussionmentioning
confidence: 99%